Análisis estético musical de la fantasía de concierto para clarinete y piano de Luigi Bassi sobre temas de la ópera Rigoletto de Verdi y su contribución en el desarrollo interpretativo del clarinete - Albán Ontaneda, John Fernando (2022)
One of the most important periods in the history of music is romanticism, it is known as the gateway between ancient music and contemporary music; in this period several musical aspects are developed due to different events that society went through. For the understanding and interpretative developments of works from this period, the musical aesthetic analysis must be taken into account, such is the case of this research that seeks to aesthetically analyze the music of Luigi Bassi's Concert Fantasy for Clarinet and Piano on themes of the Verdi's opera Rigoletto. For the development of this project, the general objective was to identify the contribution of the musical aesthetic analysis of the concert fantasy for clarinet and piano by Luigi Bassi on themes from the opera Rigoletto by Giuseppe Verdi in the interpretative development of the clarinet, therefore, it was necessary to generate information based on inquiries, being an investigation of a scientific and analytical nature. Also the analysis of the interviews carried out, which were applied to the teacher Luis Cartuche and to the clarinet teachers of the area of woodwinds of the College of Arts "Salvador Bustamante Celi" who commented on their musical approaches with the romantic period, the musical aesthetic analysis and the geographical, historical and musical context of the work under study. The same ones who agree that it is a little-known work and for its total understanding, an aesthetic musical analysis must be carried out, the same one that allows a good interpretive development. It is concluded that Luigi Bassi's Concert Fantasia for Clarinet and Piano on themes from Verdi's opera Rigoletto belonging to the romantic period, is a work that reflects the European society of the 19th century that for its interpretation everything related to it must be analyzed. the same. Being an adaptation, what happens in the opera must be understood in the first instance, so that later, with the philosophical thoughts of the time, the adaptation itself can be understood and a correct interpretation achieved. 5 It is recommended to clarinet players that, for a good interpretation, a musical aesthetic analysis must be carried out, where the context is developed, encompassing the geographical, the socio-historical, the composer, philosophical thoughts, among others. You should also have an approach with other musicians that help to understand in depth the work under study, as well as techniques that allow its development and in this case the interpretation of the clarinet.